Islam and advertising: the ideal stakeholder perspective - Mokhtar, Aida; Samsudin, Sofiah (Graduate School of Communication Arts and Management Innovation, National Institute of Development Administration, 2015)
The collective responsibility of stakeholders in the making of responsible advertisements is the essence of the multiple perspectives for responsible advertising by Polonsky & Hyman (2007) that is based on the stakeholder theory. This research study aims to contribute to current literature by defining the ideals of responsible advertisements from the Islamic perspective. The purpose of this research study is to examine the concept of Islamic advertising as what it should be rather than what is already practised as Islamic advertising. This qualitative study involves the interviewing of academicians with an Islamic background. The key findings suggest that Islamic advertising can be comparable to propagation if it adheres to the principles of da’wah, is centred on tawḥīd, promotes ḥalāl products and is Shari’ah compliant. The challenge was in defining Islamic advertising as there is seemingly a paradox regarding the association of advertising whose conception was inspired by commercialism, whilst Islam promotes the view of propagation and moderation in consumption. It is hoped that this research study has contributed to current studies on stakeholder theory and defined Islamic advertising in view of Malaysia’s position as the Global Halal Hub.